Biochanin A Reduces Inflammatory Injury and Neuronal Apoptosis following Subarachnoid Hemorrhage via Suppression of the TLRs/TIRAP/MyD88/NF-κB Pathway. (3rd June 2018) - Wu, Ling-yun; Ye, Zhen-nan; Zhuang, Zong; Gao, Yongyue; Tang, Chao; Zhou, Chen-hui; Wang, Chun-xi; Zhang, Xiang-sheng; Xie, Guang-bin; Liu, Jing-peng; Zhou, Meng-liang; Hang, Chun-hua; et al.
Abstract : Inflammatory injury and neuronal apoptosis participate in the period of early brain injury (EBI) after subarachnoid hemorrhage (SAH). Suppression of inflammation has recently been shown to reduce neuronal death and neurobehavioral dysfunction post SAH. Biochanin A (BCA), a natural bioactive isoflavonoid, has been confirmed to emerge the anti-inflammatory pharmacological function. This original study was aimed at evaluating and identifying the neuroprotective role of BCA and the underlying molecular mechanism in an experimental Sprague-Dawley rat SAH model. Neurobehavioral function was evaluated via the modified water maze test and modified Garcia neurologic score system. Thus, we confirmed that BCA markedly decreased the activated level of TLRs/TIRAP/MyD88/NF- κ B pathway and the production of cytokines. BCA also significantly ameliorated neuronal apoptosis which correlated with the improvement of neurobehavioral dysfunction post SAH. These results indicated that BCA may provide neuroprotection against EBI through the inhibition of inflammatory injury and neuronal apoptosis partially via the TLRs/TIRAP/MyD88/NF- κ B signal pathway.